The information content of monetary statistics for the Great Recession: Evidence from Germany - Wenjuan Chen; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
This paper introduces a Divisia monetary aggregate for Germany and explores its information content for the Great Recession. Divisia money and the corresponding simple sum aggregate are highly correlated in normal times but begin to diverge before the crisis. Out of sample forecast analysis and a conditional forecast exercise show that the predictive content of this divergence for the Great Recession is not only statistically significant, but also economically important.
Keywords: E27; E32; E51; C43; 330; Monetary aggregates; Divisia index; recession indicator; Great Recession